In whose best interests? Regulating childcare environments in Australia. Issue 4 (December 2021) - Morrissey, Anne-Marie; Moore, Deborah
This conceptual model paper uses systems theory to explain how key elements in the Australian policy and regulatory context lead to three issues of concern in childcare centre physical environments: siting of centres on busy roads; lack of outdoor space; and, emergency evacuation in high-rise buildings. Drawing on evidence from prior studies and policy documents through desktop research, as well as childcare centre visits and communications with stakeholders and experts, we confirmed these issues as threats to children's health, safety, development and well-being. Adapting Goekler's 'iceberg model' of systems theory, we identified a dominance of commercial childcare property interests and complex and conflicting policy and regulatory structures, as explanatory elements leading to outcomes that conflict with children's best interests.